Social Support Mediates the Relationship between Placement Anxiety and Counterproductive Behavior in Non-commissioned Officer Students at SPN Tjilik Riwut Polda Kalteng - Ayunda, Gusti Astrid Rizkianti Dwi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine Social Support Mediates the Relationship Between Placement Anxiety and Counterproductive Behavior in Noncommissioned Officer Students at SPN Tjilik Riwut Central Kalimantan Regional Police. The data analysis technique used multiple linear regression and the results showed that there was a relationship between placement anxiety and counterproductive behavior mediated by social support. Based on the results of the research that has been conducted using regression analysis, it can be concluded that there is a positive relationship between anxiety about placement and counterproductive behavior of Bintara students at SPN Tjilik Riwut Polda Kalteng.